Structuralism Perspective to Interpret the Patterns and Meanings Found in Vernacular Architecture - Lake, Reginaldo Christophori; Jeraman, Pilipus (University of Merdeka Malang, 2023)
Patterns and meanings are one of the formal architectural objects commonly studied by academics and practitioners. However, the philosophy, theory, and concept of structuralism underlying architectural patterns and meanings as a complex and diverse issue have not been conducted. Therefore, it is important to carry out in-depth studies in the context of structuralism on these objects. This theoretical study reveals the relationship between vernacular architectural patterns and the influencing philosophical, theoretical, and paradigm factors using the literature review method. Based on the notion of structural thought elaborated with architectural theory in the context of form, function, and meaning, three approaches were formulated, namely formalist, genetic, and dynamic structural approaches to reading architectural patterns and traditional meaning forms. The results showed that this study has succeeded in presenting a new reading tool to parse the patterns and meanings of a relatively complete vernacular architecture starting from the philosophical, theoretical context to the underlying paradigm. These results are expected to be useful as a new reading tool for vernacular architectural patterns. Similarly, the expected implication is as a modern architectural design method.